Which Prosthetic Foot to Prescribe?: Biomechanical Differences Found during a Single-Session Comparison of Different Foot Types Hold True 1 Year Later. Issue 1 (January 2017) - De Asha, Alan Richard; Barnett, Cleveland T.; Struchkov, Vasily; Buckley, John G.
ABSTRACT: Introduction: Clinicians typically use findings from cohort studies to objectively inform judgments regarding the potential (dis)advantages of prescribing a new prosthetic device. However, before finalizing prescription, a clinician will typically ask a patient to "try out" a change of prosthetic device while the patient is at the clinic. Observed differences in gait when using the new device should be the result of the device's mechanical function but could also conceivably be a result of patient-related factors, which can change from day to day and can thus make device comparisons unreliable. To determine whether a device's mechanical function consistently has a more meaningful impact on gait than patient-related factors, the present study undertook quantitative gait analyses of an individual with a transtibial amputation walking using two different foot-ankle devices on two occasions over a year apart. If the observed differences present between devices, established using quantitative gait analysis, were in the same direction and of similar magnitude on each of the two occasions, this would indicate that device-related factors were more important than patient-related factors. Materials and Methods: One adult man with a unilateral transtibial amputation completed repeated walking trials using two different prosthetic foot devices on two separate occasions, 14 months apart. Walking speed and sagittal plane joint kinematics and kinetics for both limbs were assessed on each occasion. Clinically meaningful differences in these biomechanical outcome variables were defined as those with an effect size difference ( d ) between prosthetic conditions of at least 0.4 (i.e., medium effect size). Results: Eight variables, namely, walking speed, prosthetic ankle peak plantarflexion and dorsiflexion, and peak positive power and residual knee loading response flexion, peak stance-phase extension and flexion moments, and peak negative power, displayed clinically meaningful differences ( d > 0.4) between foot devices during the first session. All eight of these showed similar effect size differences during the second session despite the participant being heavier and older. Conclusions: Findings suggest that a prosthetic device's mechanical function consistently has a more meaningful impact on gait than patient-related factors do. These findings support the current clinical practice of making decisions regarding prosthetic prescription for an individual based on a single-session evaluation of his/her gait using two different devices. However, to confirm this conclusion, a case series using the same approach as the present study could be undertaken.